Raising the Issue of Local Wisdom in Science Learning and Its Impact on Increasing Students' Scientific Literacy - Ni Nyoman Sri Putu Verawati; Wahyudi Wahyudi (Faculty of Engineering and Applied Science, 2024)
In the context of global educational challenges, scientific literacy remains a foundational goal yet is often hindered by traditional teaching methods that lack cultural and contextual relevance. This study addresses the intersection of local wisdom with science education as a strategy to enhance students' scientific literacy, grounded in the belief that culturally resonant teaching can improve learning outcomes. This study explores the impact of integrating local wisdom into science education on enhancing students' scientific literacy. Employing an experimental pretest-posttest control group design, the research involved 86 Indonesian high school students, divided evenly between a control group receiving traditional science instruction and an experimental group whose curriculum was enriched with local wisdom content. Over a six-week period focused on climate change, the experimental group's instruction intertwined indigenous knowledge with scientific concepts, aiming to create a culturally contextualized learning experience. The results, derived from quantitative measures were analyzed using ANOVA and post hoc tests. Findings indicate a statistically significant improvement in the scientific literacy of the experimental group compared to the control group, with the former demonstrating a substantial increase in posttest scores. The study confirms that local wisdom can be a potent tool in science education, leading to higher engagement and improved scientific literacy. This research contributes to the field by providing empirical evidence supporting culturally responsive teaching approaches and underscores the potential of local wisdom in bridging the gap between traditional knowledge systems and scientific methodologies.